Atividade turística e desenvolvimento econômico na Região Nordeste do Brasil - Francisca Diana Ferreira Viana (2010)
From 1990, intensified in the Northeast region of Brazil, the volume of investments designed to leverage the tourism industry with the creation of the Tourism Development in the Northeast (NE PRODETUR). The result of these investments has been a substantial improvement in the indicators characterizing the tourism activity. However, despite this improvement, the main contribution of tourism of tourism activity that characterizes Lodging and Food regional GDP, has shown a decrease. In this context, the objective of this thesis was to answer this question we applied the theoretical construction of the Cost Disease and found that the activity room and board, used as a proxy for tourism, has a productivity gap towards to other sectors of economic activity. This gap should be associated with low activity has this ability to absorb technological improvements. This finding becomes therefore clear limitation that tourism has to be an instrument of development for the Northeast region. This thesis consists of four tests: the first using data from the World Travel & Tourism Council (WTTC) and the Brazilian Institute of Geography and Statistics (IBGE) makes a presentation on the evolution and the accounts of tourism in the world, regions and countries selected. The second essay focuses on theoretical approaches that explain tourism as an instrument of economic development and is also an explanation of the recent overview of the Brazilian tourism. In the third trial, taking as reference the Northeast region in contrast to Brazil, we applied thetheoretical construction of the Cost Disease activity classified by IBGE. Finally, the fourth trial, using a methodology Computable Equilibrium (CGE), was simulated economic impact that PRODETUR II would bring to Northeast Region.